THE ROLE OF HYDROTHERMAL FLUIDS IN THE PRODUCTION OF SUBDUCTION ZONE MAGMAS: EVIDENCE FROM SIDEROPHILE AND CHALCOPHILE TRACE ELEMENTS AND BORON - Noll Jr.P.D.; Newsom H.E.; Leeman W.P.; Ryan J.G. (My University, 1996)
In order to evaluate the processes responsible for the enrichments of certain siderophile/ chalcophile trace elements during the production of subduction-related magmas, representative lavas from seven subduction zones have been analyzed for Pb, As, Sb, Sn, W, Mo, Tl, Cu, and Zn by inductively coupled plasma-mass spectrometry (ICP-MS), radiochemical epithermal neutron activation analysis (RENA), and atomic absorption (AA). The siderophile/chalcophile elements are compared to the highly fluid-mobile element B, the light rare earth elements (LREEs), U, and Th in order to place constraints on their behavior in subduction zones. Boron, As, Sb, and Pb are all enriched in arc lavas and continental crustal rocks more so than expected assuming normal magmatic processes (melting and crystallization). Tin, W, and Mo show little evidence of enrichment. Correlations of Pb/Ce, As/Ce, and Sb/Ce with B/La are statistically significant and have high correlation coefficients (and, more importantly, slopes approaching one) suggesting that Pb, As, and Sb behave similarly to B (i.e., that they are fluid-mobile). In addition, across-arc traverses show that B/La, As/Ce, Pb/Ce, and Sb/Ce ratios decrease dramatically with distance towards the back-arc basin. W/Th, Tl/La, Sn/Sm, and Mo/Ce ratios and Cu and Zn concentrations have much less systematic across-arc variations and correlations with B/La are not as strong (and in some cases, not statistically significant) and the regression lines have much lower slopes. Mixing models between upper mantle, slab-derived fluid, and sediment are consistent with a fluid-derived component in the arcs displaying extra enrichments of B, Pb, As, and Sb. These observations imply efficient mobilization of B, Pb, As, Sb, and possibly Tl into arc magma source regions by hydrothermal fluids derived from metamorphic dehydration reactions within the slab. Tin, W, and Mo show little, if any, evidence of hydrothermal mobilization. Copper appears to be slightly enriched in arc lavas relative to mid-ocean ridge basalts (MORBs) whereas Zn contents of arc lavas, MORB, ocean island basalts (OIBs), and continental crustal samples are similar suggesting that the bulk partition coefficient for Zn is approximately equal to one. However, Zn contents of the upper mantle are lower than these reservoirs implying an enrichment of the source region in Zn prior to melting.These nonigneous enrichments have implications not only for arc magma genesis but also for continental crust formation and crust-mantle evolution. The mobility of Pb, As, Sb, and B in hot, reducing, acidic hydrothermal fluids may be greatly enhanced relative to the large-ion lithophile elements (LILEs; including U) as a result of HS−, H2S, OH−, or other types of complexing. In the case of Pb, continued transport of Pb from subducted slabs into arc magma source regions throughout Earth history coupled with a U fluxing of the mantle a the end of the Archean may account for the depletion of Pb in the upper mantle, the low U/Pb of most arc volcanics and continental crustal rocks, and provide an explanation for the Pb- Paradox (Hofmann et al., 1986;McCulloch, 1993;Miller et al., 1994). Recycled slabs will then retain high U/Pb ratios upon entering the deep mantle and may eventually become incorporated into the source regions of many OIBs; some with HIMU (high 238U/204Pb) signatures.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей